2011
DOI: 10.2460/javma.239.10.1325
|View full text |Cite
|
Sign up to set email alerts
|

Mass-to-splenic volume ratio and splenic weight as a percentage of body weight in dogs with malignant and benign splenic masses: 65 cases (2007–2008)

Abstract: Results suggested that mass-to-splenic volume ratio and splenic weight as a percentage of body weight may be useful in differentiating between hemangiosarcoma and benign lesions in dogs with splenic masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 12 publications
1
37
4
Order By: Relevance
“…Marked focal contrast accumulation in hemangiosarcomas was reported recently, possibly representing contrast medium in wide vascular spaces within these tumors . Splenic malignant neoplasms, most of which are hemangiosarcomas, frequently contain extensive hemorrhage or necrosis and so may be difficult to distinguish from hematoma on the basis of either gross or histologic examination . As noted above with respect to hepatic masses, other imaging techniques that depict vascularity of tissues also have limited potential to distinguish the histologic types of splenic mass …”
Section: Discussionmentioning
confidence: 99%
“…Marked focal contrast accumulation in hemangiosarcomas was reported recently, possibly representing contrast medium in wide vascular spaces within these tumors . Splenic malignant neoplasms, most of which are hemangiosarcomas, frequently contain extensive hemorrhage or necrosis and so may be difficult to distinguish from hematoma on the basis of either gross or histologic examination . As noted above with respect to hepatic masses, other imaging techniques that depict vascularity of tissues also have limited potential to distinguish the histologic types of splenic mass …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported approximately 70% of dogs with non-traumatic hemoperitoneum had hemangiosarcoma [13]. Hemoperitoneum is reported in 63–80% of dogs with hemangiosarcoma, compared with only 30% of dogs with benign splenic masses [4, 5]. This has led to the ‘double 2/3 rule,’ which is currently used to give owners a prediction of the odds of each of the possibilities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify repeatable measures or other techniques that might distinguish malignant from benign masses [5, 914]. For instance, mass-to-splenic volume ratio and splenic weight as a percentage of body weight have been used to differentiate malignant from benign splenic lesions, with hemangiosarcoma masses being smaller in both categories [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations